La reforma del mercado de trabajo en España durante la crisis financiera internacional - Ojeda, Antonio (2012)
The labor market reform in Spain during the international financial crisis The crisis emerged in 2008 has caused a marked degradation of employment in Spain and an emergency legislation in a very short time, which is analyzed in the study.